2011
DOI: 10.1142/s0218194011005116
|View full text |Cite
|
Sign up to set email alerts
|

Time-Aware and Weighted Fault Severity Based Metrics for Test Case Prioritization

Abstract: Test metrics succeed in analyzing the current level of maturity in testing and give a projection on the way to proceed with testing activities by allowing us to set goals and predict future trends. The objective of test metrics is to capture the planned and actual quantities: the effort, time and resources required to complete all the phases of development of the software project. Test case prioritization is an effective and practical technique in regression testing. It schedules test cases in order of precede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…To address regression testing from specification modeling, Mary and Krishnamoorthi [45] have proposed a metricbased approach on the varying priorities of requirements, test cases, and execution time of test cases for prioritization of test cases. The main aim of proposing the "Average percentage of Severe Fault Detection per Time" (ASFD T ) metric [45] has been to evaluate the prioritized testing empirically, depending on the varying prioritization of requirements. Results of the proposed metric indicated that all other techniques (function coverage, statement coverage and requirement-based prioritization) outperformed the random ordering technique.…”
Section: Model-based Test Case Prioritizationmentioning
confidence: 99%
See 4 more Smart Citations
“…To address regression testing from specification modeling, Mary and Krishnamoorthi [45] have proposed a metricbased approach on the varying priorities of requirements, test cases, and execution time of test cases for prioritization of test cases. The main aim of proposing the "Average percentage of Severe Fault Detection per Time" (ASFD T ) metric [45] has been to evaluate the prioritized testing empirically, depending on the varying prioritization of requirements. Results of the proposed metric indicated that all other techniques (function coverage, statement coverage and requirement-based prioritization) outperformed the random ordering technique.…”
Section: Model-based Test Case Prioritizationmentioning
confidence: 99%
“…While FP and RV factors were not proposed for the TCP approach, that is why the results of the study cannot be generalized because more test cases prioritization factors exist in the literature. To prioritize test cases using test case execution time and the number of test cases is beneficial for the identification of maximum faults [45]. However, the challenge is the consumption of time on the execution of test cases which do not recover errors in a test suite.…”
Section: Limitations or Challenges Of Existing Fr-based Techniquesmentioning
confidence: 99%
See 3 more Smart Citations